ESTOQUE DE CARBONO E AGREGAÇÃO DO SOLO EM SISTEMAS CONVENCIONAIS E INTEGRADOS DE PRODUÇÃO AGROPECUÁRIA - Luiz Aivi Oshiro , Jorge; Guilherme da Silva Farias , Paulo; Beatriz da Silva Souza , Camila; Teresa Alves Sousa , Maria; Romeiro Araújo , Alexandre; Antonio Schiavo, Jolimar (ANAIS DO ENIC, 2026)
-